Linking Weather and Phenology to Stopover Dynamics of a Long-Distance Migrant - Carneiro, Camilo; Gunnarsson, Tómas G.; Alves, José A. (Frontiers in Ecology and Evolution, 2020)
For many migratory species, migration can represent a significant part of the annual cycle and the strategies used to move between the breeding and non-breeding areas vary considerably. Weather conditions are important during migration, particularly wind and temperature, and can play a crucial role in the timing of events during the annual cycle of migratory birds. When timing of specific events is important, for example spring arrival and laying dates, the effects of weather on the previous migration might lead to important fitness consequences, as it may alter migration speed. During spring, Icelandic whimbrels Numenius phaeopus islandicus display two main migratory behaviours: a direct flight from the wintering to the breeding sites (direct migration), or, more commonly, two flights with one stopover (stopover migration). We investigated how wind conditions, temperature and spring departure date may drive individuals to adopt either migratory behaviour. Interestingly, we found no differences in wind support during migratory flights, in temperature closer to Iceland or on crosswinds experienced in the region before reaching the main stopover areas. However, when individuals undertook a direct flight, departure date from the wintering sites was on average later, but this was not explained by wind patterns over a period of seven days prior to departure. In addition, we explored the variation at the individual level for three birds that changed migratory behaviour between years. The differences in all variables for these individuals reflected the variation observed at the population level. Overall, in such long migrations, it seems advantageous to perform a shorter flight to a stopover area, from where the weather conditions in the breeding areas may be assessed and avoid the risk of facing stochastic inclement weather prior to breeding, while synchronising time of arrival with conspecifics. In contrast, direct flights seem more common when individuals are time pressed.